Community of independence: a communal sustainability centre in Soweto - Brynard, Jeremia (My University, 2023)
South Africa is a country with a history that tells a story of struggle, oppression, revolution, and freedom. Over the centuries the people of South Africa have seen many rulers and have known many masters but have now finally obtained freedom through democracy. The township of Soweto is no different as they were once oppressed and marginalized but, through collective strength and determination, rose and obtained their freedom. The people of Soweto have proven that they can empower themselves through means of community, thus making the communities of Ekhaya prime candidates for this dissertation. This dissertation will question the possibility of affecting tangible social, political, and economic change within an already established and previously oppressed urban landscape through communal empowerment and socio-economic independence. The proposed intervention targets the communities of Ekhaya through the revitalization of the decommissioned Orlando Power Station within Soweto. The intervention results from the close social, political, and environmental analysis that is the culmination of research done on themes such as community, empowerment, and independence within the context of the Ekhaya communities. This dissertation is divided into five phases that are representative of the architectural design process: Data Acquisition, Problem Definition, Ideation, Prototyping, Implementation. The Data Acquisition phase introduces the proposed intervention’s site, surrounding context and initial observations. To reach the communities of Ekhaya research needs to be done in order to identify the optimal location. This phase will depict the existing urban framework of Orlando East and the context surrounding the communities of Ekhaya and the chosen site. The following phase will attempt to Define The Problems identified within the targeted area of study and initialize an approach towards understanding these problems and how they could be addressed. Once a proper investigation of the target area has been concluded, we will identify areas of concern that require better understanding through further research. The Ideation phase addresses the identified problems through means of academic research and argumentative deliberation. Here the topics identified in the previous phase will be unpacked and argued to obtain a viable solution to be implemented through means of an architectural intervention. Following this, the Prototyping phase will aim to conceptually explore the research findings physically to move closer to a design solution. It will be shown how research can be transformed into conceptual models that will later serve as a basis for design. Furthermore, the Implementation phase will attempt to manifest all previous findings into a physical built form that will be inclusive of community, provide empowerment, and inspire independence.
A dissertation submitted to the School of Architecture and Planning, University of Witwatersrand, in partial fulfilment of the degree of Master’s of Architecture (Professional), 2022